Targeting glucose metabolism to suppress cancer progression: prospective of anti-glycolytic cancer therapy - Abdel-Wahab, Ali F.; Mahmoud, Waheed; Al-Harizy, Randa M. (Pharmacological research, 2019)
[Display omitted] •Cancer is the second major cause of mortality worldwide despite current chemotherapy.•Targeting aerobic glycolysis has become a research focus for developing anticancer drugs.•These antiglycolytic agents might also sensitize tumor cells to other cytotoxic therapies.•Although preclinical studies are promising, antiglycolytic therapy has not yet been translated into clinical practice.•This review presents the current state of glycolytic cancer therapy discussing the challenges and opportunitie. Most solid tumor cells adapt to their heterogeneous microenvironment by depending largely on aerobic glycolysis for energy production, a phenomenon called the Warburg effect, which is a hallmark of cancer. The altered energy metabolism not only provides cancer cell with ATP for cellular energy, but also generate essential metabolic intermediates that play a pivotal role in the biosynthesis of macromolecules, to support cell proliferation, invasiveness, and chemoresistance. The cellular metabolic reprogramming in cancer is regulated by several oncogenic proteins and tumor suppressors such as hypoxia-inducible factor (HIF-1), Myc, p53, and PI3K/Akt/mTOR pathway. A better understanding of the mechanisms involved in the regulation of aerobic glycolysis can help in developing glycolytic inhibitors as anticancer agents. These metabolic antiglycolytic agents could be more effective if used in drug combinations to combat cancer. Several preclinical and early clinical studies have shown the effectiveness of targeting the glycolytic pathway as a therapeutic approach to suppress cancer progression. This review aimed to present the most recent data on the emerging drug candidate targeting enzymes and intermediates involved in glucose metabolism to provide therapeutic opportunities and challenges for antiglycolytic cancer therapy.